1069 ESSENTIAL FRAILTY TOOLSET AS A PREDICTOR OF PROLONGED LENGTH OF STAY AND DISCHARGE DESTINATION AFTER TRANSCATHETER AORTIC VALVE IMPLANTATION. (14th June 2022) - Patel, N; Teh, W; Omoniyi, O; Martin, W; Weir-McCall, J; D'Errico, L; O'Sullivan, M; Davies, W; Costopoulos, C; Costanzo, P
Abstract: Introduction: Frailty is associated with poor outcomes following transcatheter aortic valve implantation (TAVI). Rockwood is the widely used score for this population. In a recent trial, a more objective score, the Essential Frailty Toolset (EFT) outperformed Rockwood's in predicting mortality and disability 1-year post-TAVI. Whether it predicts in-hospital length of stay (LOS) and discharge destination post-TAVI remains unclear. Method: A cohort of patients undergoing TAVI for aortic stenosis was recruited, demographic characteristics collected, and frailty assessed with EFT and Rockwood scores. Primary outcomes were LOS post-TAVI, categorised as 'not prolonged' (≤2 days) or 'prolonged' (>2 days) and discharge destination, characterised as 'home' or 'non-home'. Results: 86 patients were recruited, with median age 82 years (IQR 78–86). 54% were male. EFT identified 35% and Rockwood 11% as frail. 19% were cognitively impaired. 5 chair rises were completed by 70%, with 30% managing under 15 seconds. Median haemoglobin was 121 g/L (IQR 109.5–136). Median albumin was 36 g/L (IQR 33–39). 84% of procedures were transfemoral. 20% had moderate–severe left ventricular systolic dysfunction. Median LOS post-TAVI was 2 days (IQR 2–5). 94% were discharged home, 6% to referring local hospital or rehabilitation centre. 46% were NYHA class III-IV. A model for prolonged LOS including comorbidities, showed frailty determined by EFT (OR 4.80, CI 95% 1.52–15.2, p = 0.008) but not Rockwood (OR 5.00, CI 95% 0.865–29.0, p = 0.072) was the only significant independent predictor for prolonged LOS. A model adjusting for comorbidities also showed EFT to be an independent predictor for non-home discharge destination of borderline significance (OR 2.57 CI 95% 0.994–6.66, p = 0.051) but Rockwood was not (OR 1.38 CI95% 0.485–3.91, p = 0.548). Conclusion: In a real-world elderly population, EFT score was a stronger, more independent predictor of prolonged LOS and non-home discharge post-TAVI, than Rockwood's. EFT would be an effective pre-operative assessment tool for LOS and discharge destination for TAVI.